1995
DOI: 10.1021/bi00038a010
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding and Protein Dynamics in Cupredoxins

Abstract: Type 1 copper sites bind nitric oxide (NO) in a photolabile complex. We have studied the NO binding properties of the type 1 copper sites in two cupredoxins, azurin and halocyanin, by measuring the temperature dependence of the ligand binding equilibria and the kinetics of the association reaction after photodissociation over a wide range of temperature (80-280 K) and time (10(-6)-10(2) s). In both proteins, we find nonexponential kinetics below 200 K that do not depend on the NO concentration. Consequently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Do both types have similar energy landscapes? Studies of the binding of NO to azurin and another "blue copper" protein, halocyanin, indeed show distributed kinetics and prove that these proteins also have statistical substates [42,43].…”
Section: The Energy Landscape In Different Proteinsmentioning
confidence: 99%
“…Do both types have similar energy landscapes? Studies of the binding of NO to azurin and another "blue copper" protein, halocyanin, indeed show distributed kinetics and prove that these proteins also have statistical substates [42,43].…”
Section: The Energy Landscape In Different Proteinsmentioning
confidence: 99%
“…It has been reported that type 1 blue copper (T1Cu) proteins and multicopper oxidases (MCOs) can react with NO, with concomitant production of a reversible diamagnetic charge-transfer complex. 21 - 24 However, complete complex formation was only observed at very low temperatures (77 K). 23 At room temperature, only very low extent (∼10 %) of complex formation was observed, even in the presence of saturating concentrations of NO.…”
Section: Introductionmentioning
confidence: 99%
“…Many other heme proteins, for instance, cytochrome oxidase (Alben et al, 1981), cytochrome P450 (Tsubaki et al, 1986;Porter and Coon, 1991), horseradish peroxidase (Doster et al, 1987;Uno et al, 1987), and hemoglobin (Potter et al, 1990), all exhibit multiple CO stretch bands in the CO-ligated form and thus possess A substates. Taxonomic substates are also observed in other classes of protein, for example, retinal proteins and blue copper proteins (Nar et al, 1991;Ehrenstein et al, 1995). Theoretical ideas suggest that these substates are a general property of proteins (Honeycutt and Thirumalai, 1990).…”
mentioning
confidence: 97%